Assessing the Role of Health Practitioners in Promoting Physical Activity and Dietary Changes - Batool Abdullah Almogrrab; Latifah Ali Alyahyaa; Ammar Fadhel Benammar; Emad Ayesh Alsalem; Ghadeer Hassan Alkhulaif; Hanan Abdulmonem Almajed; Ali Ahmad Alnasir; Mohammed Ibrahim Alibrahim; Haidar Yusef Alzarie; Israa Mohammed Alwabari; Abdulrahim Jassim Alhassar; Adel Mohammed Almeel (International Journal of Medical Toxicology and Legal Medicine, 2024)
Lifestyle-related diseases, including obesity and cardiovascular conditions, are some of the major global health challenges brought about by bad dietary habits and physical inactivity. Traditional health interventions, often generalized and without personalization, have been largely ineffective because of low adherence, lack of follow-up, and inability to address behavioral barriers at the individual level. The paper overcomes this limitation using the BCW framework to assess the health practitioner's contribution in enhancing sustainable changes to both physical activity and dietary habits. In short, this paper sets out to develop, enact, and test tailored interventions aimed at influencing capability, opportunity, and motivation, each considered as one of the antecedents to a change of behavior. The novelty of the approach is in the integration of practitioner-led tailored strategies with self-exactable behavior change techniques supported by digital tools to monitor and provide feedback. The paper identifies a new integrated approach within the context of the roles of health professionals in developing sustainable behavior change. The study uses a mixed-methods design, which involves a combination of statistical analysis and thematic evaluation, to evaluate the effect of practitioners' strategies. The goal is to deliver data-driven insights and predictive recommendations that can fine-tune health interventions, utilizing multi-channel recruitment and a structured 15-item questionnaire. Analyzing behavioral and thematic outcomes, the research identifies factors that influence health outcomes and delivers actionable strategies for improving patient engagement and success. The findings will contribute to better understanding how personalized, continuous care can lead to better effectiveness in health promotion practice by setting the groundwork for future interventions in health behavior management.